ショウワキチ シュウヘン ノ チジキ ゼン ジリョク ブンプ - 仁木, 国雄; ニキ, クニオ; 芳野, 赳夫; ヨシノ, タケオ; 福西, 浩; フクニシ, ヒロシ; Nikki, Kunio; Yoshino, Takeo; Fukunishi, Hiroshi (1981)
P(論文) 第17次南極地域観測隊(1976-1977)では, 携帯用プロトン磁力計を用いて, 地磁気全磁力の調査を行った。測定を行った地域は, リュツォ・ホルム湾沿岸のラングホブデ, スカルブスネスの露岩地域と, 昭和基地周辺の島々および昭和基地-みずほ基地間の, S, H, Zルート上である。これらの測定データをもとに東オングル島(含ネスオイヤ), 西オングル島, テオイヤ, ラングホブデ, スカルブスネス等の地域の地磁気分布図を作製し, 地質構造との比較を行った。その結果, 磁気異常帯と地質構造の間によい対応があることが明らかになった。 Measurements of geomagnetic field intensity were carried out in the vicinity of Syowa Station (East and West Ongul Islands, Teoya, Langhovde, and Skarvsnes) and on the route between Syowa and Mizuho Stations by the 17th wintering party of Japanese Antarctic Research Expedition. The total magnetic intensity was measured on the ground by using a portable proton magnetometer, and then iso-intensity contours were drawn. From a comparison of these magnetic maps with the geological maps, it is found that there is a close correspondence between the distribution of magnetic anomaly and the geological structure. departmental bulletin paper